Assessing and Mitigating Business Risks in India - Bhasin, Balbir B (Business Expert Press, 2012)
Ebook from IG Library ; India, one of the world’s fastest-growing large economies, offers business and investment opportunities across a multitude of sectors. More and more companies around the world are eager to do business in India. This book details the challenges and risks involved as well as providing real suggestions for overcoming them.